The first evidence for Late Pleistocene hominin populations on the southern Caspian Sea coast. (20th January 2017) - Vahdati Nasab, Hamed; Roustaei, Kourosh; Ghamari Fatideh, Mohammad; Shojaeefar, Fatemeh; Hashemi Sarvandi, Milad
Abstract : The southern shore of the Caspian Sea is well known for its great potential in relation to sites of Mesolithic date (e.g. Coon 1951 ; Jayez & Vahdati Nasab 2016 ). Situated between two major geographic barriers—the Alborz Mountains to the south, and the Caspian Sea to the north—this area has been considered one of the major hominin dispersal corridors during the Pleistocene–Holocene transition (Vahdati Nasab et al . 2013 ). Furthermore, the relatively stable and mild climatic conditions, vast and lush temperate forests, and abundance of fauna and water resources have all made this region an attractive niche for human settlement.